2019
DOI: 10.3389/fpsyg.2019.02153
|View full text |Cite
|
Sign up to set email alerts
|

Brainwave Self-Regulation During Bispectral IndexTM Neurofeedback in Trauma Center Nurses and Physicians After Receiving Mindfulness Instructions

Abstract: Fifty-seven level I trauma center nurses/physicians participated in a 4-day intervention to learn relaxed alertness using mindfulness-based instructions and EEG neurofeedback. Neurofeedback was provided by a Bispectral IndexTM (BIS) system that continuously displays a BIS value (0–100) on the monitor screen. Reductions in the BIS value indicate that power in a high-frequency band (30–47 Hz) is decreased and power in an intermediate band (11–20 Hz) is increased. A wellbeing tool with four positive affect and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…They also imply that reduced BIS values were associated with a state of physiologic relaxation, increased parasympathetic nervous system activity, and decreased sympathetic nervous system stimulation. In addition to the findings of improvements in participant well-being in our BIS neurofeedback study [73], this evaluation lends further support to the notion that the BIS monitor may be a valid device for use in neurofeedback investigations. Finally, the BIS monitor may subsequently be demonstrated to be considered as a hypnometer for continuously measuring hypnotic depth, as proposed by the former Harvard University investigator Solomon Gilbert Diamond [19].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…They also imply that reduced BIS values were associated with a state of physiologic relaxation, increased parasympathetic nervous system activity, and decreased sympathetic nervous system stimulation. In addition to the findings of improvements in participant well-being in our BIS neurofeedback study [73], this evaluation lends further support to the notion that the BIS monitor may be a valid device for use in neurofeedback investigations. Finally, the BIS monitor may subsequently be demonstrated to be considered as a hypnometer for continuously measuring hypnotic depth, as proposed by the former Harvard University investigator Solomon Gilbert Diamond [19].…”
Section: Discussionsupporting
confidence: 72%
“…Supplementary evidence for BIS reductions is the evidence provided during investigations of participants watching relaxing videos [10] or trying relaxing-guided imagery [11]. The brainwave physiology of BIS reductions, and similarity to stage I sleep, implies that such participants were in a relative state of cognitive or mental relaxation [73][74][75].…”
Section: Changes In Bis Values During Hypnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness interventions that decrease general distress also affect top-down modulation ( Berkovich-Ohana et al, 2012 ; Farb et al, 2007 ; Grant et al, 2011 ; Jacobs et al, 1996 ; Travis et al, 2010 ) and even reduce SSVEP amplitude ( Schöne et al, 2018 ). A future enhanced mindfulness strategy combining simultaneous neurofeedback ( Dunham et al, 2019 ) from the visual task itself could be used to reprogram the neural circuitry responsible for MSH. Similarly, a key next step is determining whether other extant chronic pain treatments—transcranial magnetic stimulation ( Grisaru et al, 1998 ), anticonvulsants ( Harte et al, 2016 ), or antidepressants ( Sayar et al, 2005 )—could reduce MSH and these associated neural mechanisms in at-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NF was tested among high-functioning professionals in managerial positions, who reported decreased perceived stress levels and increased concentration and focus ( Fronda et al, 2019 ). In a healthcare setting, studies suggest that NF can be used to teach physicians and nurses to enter into a state of relaxed alertness and improve their wellbeing ( Dunham, 2019 ). Additionally, previous research found NF to improve cognitive workload during working memory tasks ( Mazur et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%